Immune profiling of pediatric germ cell tumors identifies key cell populations and novel therapeutic targets - Silva, Lenilson; Cardoso, Ingridy Izabella Vieira; da Cruz, Marcelo Cavalcanti; Faria, Thaíssa Maria Veiga; Martins, Gisele Eiras; Mançano, Bruna Minniti; Lopes, Luiz Fernando; Reis, Rui Manuel; Moreno, Daniel Antunes; Pinto, Mariana Tomazini (Frontiers in Immunology, 2025)
IntroductionPediatric germ cell tumors (GCTs) are rare malignancies, comprising only about 3% of childhood cancers. Despite surgery and platinum-based chemotherapy being mainstays of treatment, their effectiveness varies by tumor subtype, and long-term toxicities remain a concern. We therefore explored the immune landscape of pediatric GCTs to uncover subtype-specific immunological features and identify potential immunotherapeutic targets.MethodsThis retrospective study investigated the immune landscape of pediatric GCTs, utilizing a cohort of 17 patients, including 14 extracranial GCTs (11 ovarian, 3 testicular), three central nervous system (CNS) mixed tumors and four non-neoplastic tissues (controls).ResultsImmune profiling revealed distinct immune microenvironments across the GCT subtypes. Dysgerminomas exhibited an immune-active profile with elevated levels of T cells, CD8+ T cells, and cytotoxic cells, alongside upregulation of immune checkpoints CTLA4, TIGIT, and IDO1, suggesting potential responsiveness to checkpoint inhibitors. In contrast, yolk sac tumors displayed an immunosuppressive environment with high CD24 and PVR expression, indicative of unique immune evasion mechanisms. Embryonal carcinomas also showed high CD24 expression. An in silico analysis of adult GCTs highlighted similarities and differences with pediatric cases; IDO1 and CD24 were consistently upregulated across age groups, while CTLA4 and PVR showed variation.ConclusionOverall, this study provides new insights into pediatric GCT immunology, supporting the potential for tailored immunotherapeutic strategies targeting the distinct immune profiles of pediatric GCT histologies.